Homophobia and heteronormativity as dimensions of stigma that influence sexual risk behaviors among men who have sex with men (MSM) and women (MSMW) in Lima, Peru: a mixed-methods analysis - Amaya G. Perez-Brumer; Ryan C. Passaro; Catherine E. Oldenburg; Jonathan Garcia; Jorge Sanchez; H. Javier Salvatierra; Javier R. Lama; Jesse L. Clark (BMC, 2019)
Abstract Background Stigma differentially influences HIV and STI care among MSM, especially regarding partner notification practices. Recognizing the heterogeneous behaviors/identities within the category "MSM," we used mixed-methods to assess sexual risk behaviors among men who have sex with men only (MSMO) and behaviorally bisexual MSM (MSMW) with HIV and/or other STIs. Methods MSMO/MSMW recently diagnosed (< 30 days) with HIV, syphilis, urethritis, or proctitis completed a cross-sectional survey assessing sexual risk behaviors, anticipated disclosure, and sexual partnership characteristics (n = 332). Multivariable generalized estimating equation models assessed characteristics associated with female compared to male partners in the last three partnerships. Follow-up qualitative interviews (n = 30) probed partner-specific experiences (e.g., acts and disclosure). Results Among all participants, 13.9% (n = 46) described at least one of their last three sex partners as female (MSMW). MSMW (mean age of 31.8) reported a mean of 3.5 partners (SD = 4.5) in the past 3 months and MSMO (mean age 30.6) reported a mean of 4.6 partners (SD = 9.7) in the past 3 months. MSMW were more likely to report unprotected insertive anal sex (77.9%) than MSMO (43.1%; p < 0.01). Cisgender female partners were associated with condomless insertive sex in the last 3 months (aPR: 3.97, 95%CI: 1.98-8.00) and classification as a "primary" partnership (2.10, 1.34-3.31), and with lower prevalence of recent HIV diagnosis (0.26, 0.11-0.61). Planned notification of HIV/STI diagnoses was less common for female than for male partners (0.52, 0.31-0.85). Narratives illustrate internal (e.g., women as 'true' partners) and community-level processes (e.g., discrimination due to exposure of same-sex behavior) that position homosexual behavior and bisexual identity as divergent processes of deviance and generate vulnerability within sexual networks. Conclusions MSMW recently diagnosed with HIV/STI in Peru report varying partnership characteristics, with different partner-specific risk contexts and prevention needs. Descriptions highlight how behaviorally bisexual partnerships cut across traditional risk group boundaries and suggest that HIV/STI prevention strategies must address diverse, partnership-specific risks.